2020
DOI: 10.1038/s41419-020-2274-x
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA RUNX1-IT1 which is downregulated by hypoxia-driven histone deacetylase 3 represses proliferation and cancer stem-like properties in hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is characterised by a hypoxic microenvironment and a high rate of heterogeneity and recurrence, and the presence of cancer stem cells (CSCs) in HCC may well explain both of these pathological properties. There is mounting evidence that long non-coding RNAs (lncRNAs) participate in carcinogenesis and maintain cancer stemness of HCC cells. However, the expression modes, regulatory mechanisms and potential roles of stemness-related lncRNAs in HCC are still obscure. LncRNA RUNX1-IT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 39 publications
(50 reference statements)
1
67
0
Order By: Relevance
“…Hypoxia, which resulted from rapid tumor growth and vascular abnormality, has been identified as a critical driver of HCC progression (Jing et al, 2019). Our previous studies have demonstrated that hypoxia contributes to the growth and metastasis of HCC via regulating protein-coding genes and non-coding RNAs, such TUFT1 (Dou et al, 2019b), VASP (Liu et al, 2018), miR-1296 (Xu et al, 2017a), and RUNX1-IT1 (Sun et al, 2020). Hypoxia has been recognized as an inducer of the activation of the TLR4/MyD88/NF-κB pathway in hepatic ischemia/reperfusion injury and liver fibrosis (Kang et al, 2017;Du et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia, which resulted from rapid tumor growth and vascular abnormality, has been identified as a critical driver of HCC progression (Jing et al, 2019). Our previous studies have demonstrated that hypoxia contributes to the growth and metastasis of HCC via regulating protein-coding genes and non-coding RNAs, such TUFT1 (Dou et al, 2019b), VASP (Liu et al, 2018), miR-1296 (Xu et al, 2017a), and RUNX1-IT1 (Sun et al, 2020). Hypoxia has been recognized as an inducer of the activation of the TLR4/MyD88/NF-κB pathway in hepatic ischemia/reperfusion injury and liver fibrosis (Kang et al, 2017;Du et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a class of transcribed RNA molecules with a length more than 200 nucleotides with limited or no protein‐coding capacity 5 . Accumulating studies have reported that lncRNAs play critical roles in cancer progression and development and participate in diverse biological functions such as cell proliferation, apoptosis, stem cell differentiation, and metastasis 6,7 . The molecular mechanisms by which lncRNAs exert their biological function are diverse and complex.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence supports the hypothesis that lncRNAs participate in regulating gene transcription, mRNA stabilization, and protein synthesis and degradation [15]. Furthermore, lncRNAs have been crucial regulators in the occurrence and progression of various human cancers, including DLBCL [16][17][18][19][20][21]. The HLA complex P5 (HCP5) is a cancer-related lncRNA and has been investigated in breast cancer [22], follicular thyroid carcinoma (FTC) [23], lung adenocarcinoma (LUAD) [24], glioma [25], and GC [26].…”
Section: Ivyspring International Publishermentioning
confidence: 94%